Veljavnost odnosa sila-hitrost-moč pri simulaciji teka na smučeh z rolkami - Ribič, Ažbe (Šport (Ljubljana), 2022)
The aim of our study was to evaluate the validity of the outcome variables of the force-velocity-power (F-v-P) relationship in crosscountry roller skiing. Six elite cross-country skiers completed 30-meter sprints on two hills with slopes of 2% and 6%. Horizontal velocity and horizontal force were calculated using data from a laser distance meter. The strength of the linear relationship between force and velocity was tested using the repeated measures correlation method. We found a statistically significant linear relationship between force and velocity (p < 0,05). Velocity accounted for 50% (r2 = 0,497) of the variance of force on the hill with 2% slope and 56% (r2 = 0,558) of the variance of force on the hill with 6% slope. Our results show a lower percentage of variance explained compared to other studies that have investigated the F-v-P relationship in sprinting in track and field athletics. Based on our results, we can conclude that the validity of our results is questionable when using the novel method to test the F-v-P relationship in cross-country skiing. The presented protocol, which is time and energy efficient, is a potentially useful tool to better understand the mechanical properties of the upper body muscles of cross-country skiers. However, for the protocol to provide valid and reliable results, future studies should focus on optimizing the measurement procedure and data analyses.
Keywords: hitrost; meritve; mišice; rolkanje; šport; tek na smučeh